Customer Default, Non Performing Financing, and Divorce in Islamic Family Law - saifuddin yaqin saifuddin (Jurnal Marital: Kajian Hukum Keluarga Islam, 2026)
Customer default in Islamic financing is commonly discussed as a contractual and banking issue, particularly in relation to non performing financing. However, its social and family implications have received limited attention in Islamic family law studies. This article examines how customer default and non performing financing may contribute to marital conflict and divorce from the perspective of Islamic family law. This study uses a normative juridical approach supported by socio legal analysis of legal norms, Islamic banking principles, divorce regulations, and relevant literature on financial stress and family conflict. The findings show that customer default does not automatically cause divorce, but it may become a triggering or reinforcing factor when financial pressure affects household needs, spousal communication, trust, and the management of joint assets. In Islamic family law, such conditions may relate to the concepts of financial responsibility, harm, continuous dispute, and the failure to maintain marital harmony. The study argues that non performing financing should not be understood merely as a banking risk, but also as a social issue that may affect family stability. Therefore, Islamic financial institutions need to develop more preventive and restorative mechanisms, including financial education, restructuring, mediation, and family oriented assistance for customers experiencing payment difficulties.